ANALISIS IMPLEMENTASI KEBIJAKAN SISTEM SELF-ASSESSMENT TERHADAP WAJIB PAJAK UMKM DI KABUPATEN SEMARANG - Fabio Aryaduta; Dyah Lituhayu (Journal of Management and Public Policy, 2026)
The implementation of the self-assessment system policy constitutes a governmental effort to promote taxpayer independence, awareness, and compliance in fulfilling their tax obligations autonomously. However, in practice, the implementation of this policy continues to encounter various constraints, including limited tax literacy, low levels of taxpayer awareness, and suboptimal formal compliance. These conditions are also evident among MSME taxpayers in the Ungaran area of Semarang Regency, who still exhibit relatively limited levels of understanding, awareness, compliance, and administrative capability. This study aims to analyse the implementation of the self-assessment system policy among MSME taxpayers in Semarang Regency and to identify the factors that hinder its implementation. The research adopts a descriptive qualitative approach, with data collected through interviews, observations, and the review of official documents. The analysis of policy implementation refers to the framework proposed by Siti Kurnia Rahayu, which encompasses taxpayer understanding, awareness, compliance, administrative capability, as well as the quality of socialisation and assistance provided by implementers. Meanwhile, the inhibiting factors are analysed using the policy implementation model of Mazmanian and Sabatier, which includes problem characteristics, the ability of the policy to structure the implementation process, and environmental variables external to the policy. The findings indicate that the implementation of the self-assessment system policy among MSME taxpayers in Semarang Regency has not yet been optimal. Although taxpayers have fulfilled their tax obligations, their level of independence and awareness in calculating, paying, and reporting taxes has not been fully established. Consequently, taxpayer compliance tends to remain formalistic and dependent on the supervision of tax authorities. This condition is clearly inconsistent with the intended objectives of the policy implementation.